138 Short Sleep and Insomnia as Independent Predictors of Obesity, Hypertension, and Diabetes. (3rd May 2021) - Knowlden, Adam; Grandner, Michael
Abstract: Introduction: Epidemiological evidence of short sleep's (<6 hours) association with negative cardiometabolic health outcomes continues to mount; yet, the complex relationship between sleep and health is still not well-understood. Sleep problems, such as short sleep and insomnia, are often analyzed as a singular construct at the population level; however, it has been proposed that, although these two sleep problems likely overlap, they are separate phenomena. The purpose of this study was to: (1) determine if short sleep and insomnia were independent constructs; and to (2) evaluate whether short sleep and insomnia predicted obesity, hypertension, and diabetes. Methods: Analyses were based on the 2015-2016 National Health and Nutrition Examination Survey (NHANES). NHANES employs a complex, multistage, probability sampling design to survey a representative sample of non-institutionalized U.S. adults (≥18 years). Data related to short (<6), normal (7-8), and long (9+) sleep duration, insomnia (present: mild, moderate, severe), hypertension (present: previous hypertension/hypertension medications/blood pressure in the hypertensive range), and diabetes (present: history of diabetes/fasting blood sugar of 130+) were extracted for analysis. Age, sex, and obesity (body mass index, 30.0+) were entered as covariates into the models. Results: Among the subjects, 0.08% were normal sleepers with insomnia; 0.21% were short sleep with insomnia; and, 0.59% had insomnia with short sleep. Short sleep without insomnia (OR=1.35; p<.001), normal sleep with insomnia (OR=1.56; p<.001), and short sleep with insomnia (OR=1.64; p<.001) uniquely predicted obesity. As well, short sleep without insomnia (OR=1.23; p=0.004) as well as short sleep with insomnia (OR=1.21; p<0.001) independently predicted hypertension. Furthermore, short sleep with (2.01; p<0.001) and without (OR=1.48; p<0.001) insomnia as well as normal sleep with insomnia (p=0.007) uniquely predicted diabetes. Conclusion: Findings from this study suggested short sleep and insomnia are independent constructs, uniquely predicting obesity, hypertension, and diabetes. Short sleep and insomnia neither mediated nor moderated one another, implying these two sleep outcomes are not additive in nature, but are instead separate health problems. The distinction between short sleep and insomnia may have important epidemiological and clinical implications. Support (if any): N/A